Life on Chure and Siwalik Under the Extreme Threat of Lightning - Sharma, Shiram; KC, Hari Bahadur; Neupane, Bishnu; Dhakal, Suman (Amrit Research Journal, 2020)
Of all the natural disasters in Nepal, lightning is the second highest killer after earthquake. According to the data available from the Disaster Risk Reduction (DRR) portal of Ministry of Home Affairs (MoFA), an average of 108 people are killed by lightning each year. As would be expected, fatalities over the high mountains are rare due to both low population and low lightning flash density. Surprisingly, most fatalities and injuries are reported over the hilly areas of the Siwalik and Chure range in the middle of Nepal, despite the southern region having both a significantly higher population and higher lightning flash density. The higher fatalities over the Chure and Siwalik can be attributed to their elevation leading to a smaller distance to the charge center in the cloud and meteorological conditions that may arise for the development of a turbulence in the lee waves at the interface of southern plains and middle hills.